2008
DOI: 10.1889/jsid16.10.1009
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing displays by their temporal aperture: A theoretical framework

Abstract: Abstract— The spatio‐temporal aperture and sample rate of a video display determines both the static and dynamic resolution of the video signal that is rendered. The dynamic display characteristics like the visibility of large‐area flicker, motion judder, and motion blur can be derived from the frame rate and the temporal extent of the pixel aperture (i.e., the temporal aperture). For example, liquid‐crystal displays (LCDs) have an aperture that is relatively small in the spatial dimension and wide in the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…9 Heesch et al showed that the temporal aperture, or the temporal extent of the pixel aperture, can be used to predict flicker, motion blur, and judder. 5 The work analyzed the effect of the temporal aperture on spatiotemporal aliases to show that short duty cycles reduce the appearance of blur but increase the visibility of flicker. This is consistent with our result.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…9 Heesch et al showed that the temporal aperture, or the temporal extent of the pixel aperture, can be used to predict flicker, motion blur, and judder. 5 The work analyzed the effect of the temporal aperture on spatiotemporal aliases to show that short duty cycles reduce the appearance of blur but increase the visibility of flicker. This is consistent with our result.…”
Section: Figurementioning
confidence: 99%
“…The majority of liquid‐crystal displays (LCDs) and organic light‐emitting diode displays (OLED) on the market utilize frame rates of 60 frames per second (Hz), producing little flicker and relatively smooth apparent motion. However, there is clear theoretical and empirical evidence that higher frame rates are needed to produce smooth motion for the gamut of typical object speeds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This temporal step response is then convolved with a pulse of duration equal to the hold time (for an LCD, typically one frame), to obtain another version of the METP. [5][6][7][8] We call this the temporal step (TS) method. This last method relies on an assumption that all pixels are independent.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…Such a modulation with half the refresh rate could be lower than the critical flicker frequency for humans [24]. The reason why it is not perceived nevertheless is that LCD panels invert the polarity of their single dots in a spatially anti–phasic manner for neighboring pixels so that the oscillations cancel out.…”
Section: Introductionmentioning
confidence: 99%